43 Micra transcatheter pacing system implantation and outcomes in a single centre. (30th September 2020) - Connellan, D; Brady, C; Ryan, P; Walsh, K; Keaney, J
Abstract : Introduction and Objectives: Traditional cardiac pacemakers incorporate transvenous leads. Recently leadless pacemakers have been approved. The Micra™ pacemaker is such a device which is inserted percutaneously via the femoral vein into the right ventricle. The device is capable of providing single chamber pacing, sensing and accelerometer based rate response. Our objective was to evaluate indications, electrical parameters at insertion, complications and follow-up of 21 patients between 2017 and 2019 who underwent Micra™ pacemaker insertion at our institution. Methods: This was a retrospective, observational study. All patients who had a Micra™ pacemaker insertion in MMUH between 2017 and 2019 were included. Patient data was extracted from electronic hospital records. Results: 21 patients (61.9% male) had a Micra pacemaker implanted (table 1 ). The mean age was 42.7 ± 17.7 years (range, 19–81). Patient co-morbidities included cardiomyopathy (71.4%) previous history of intracardiac lead (33.3%), right sided valve surgery (19%), chronic kidney disease (14.3%), previous stroke (9.5%), diabetes (9.5%), and previous device infection (9.5%). The most common underlying cardiomyopathy was congenital cardiac disease (61.9%). 7 patients had underlying valvular heart disease (33.3%) and 1 patient had non-ischaemic dilated cardiomyopathy. All 21 Micra pacemaker devices were implanted successfully. 80.1% of devices were inserted into the right ventricular septum, with 2 devices inserted into the apex and the right ventricular outflow tract. 18 devices were successfully positioned on first attempt and 3 devices required repositioning (14.3%). There was one complication recorded. This was a pericardial effusion with tamponade, in a patient who was also undergoing lead explant. 3 patients had been lost to follow-up, with device checks occurring in other centres. 2 patients had died. The maximum duration of follow up was 2.9 years since first implant (Median duration 15.7 ± 8.3 months). There were no cases of device migration or failure. Mean R wave sensing was 13.7 ± 5.8 mV. 16 of the 18 patients had a threshold ≤ 1V. Two patients were noted to have higher thresholds (2.88 mV and 3.25 mV). (Table 2 ). Conclusion: In our patient cohort, use of Micra™ transcatheter pacemaker insertion was a safe alternative to conventional pacemaker insertion. The minimally invasive implantation was associated with a low acute complication rate and acceptable pacing parameters at follow-up. Longer term follow-up is ongoing.